Nigeria : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper examines the role of lower oil prices in the recent deterioration in Nigeria's macroeconomic indicators, the impact on corporate and financial sector performance. and the forward-looking aspects of promoting job-intensive growth and strengthening state and local government finances. Although the slump in oil prices contributed to sluggish growth, the lack of foreign exchange weakened corporate performance, setting the stage for nonperforming loans. Structural reforms to improve the business environment can have a positive impact on growth, while fiscal reforms would help strengthen finances of subnational governments.